The Role of The Women's Empowerment and Child Protection Office of Southwest Aceh Regency in Handling Cases of Sexual Violence Against Children - Saputra, Hijrah; A'la Salna, Nurul (Jurnal Ilmiah Teunuleh, 2025)
Sexual violence against children is a severe crime that affects their physical, psychological, and social well-being. This study explores the role of the Women's Empowerment and Child Protection Agency (DP3A) through a case study approach to evaluate the effectiveness of policies and programs, as well as the challenges faced in child protection efforts. The research aims to analyze DP3A's involvement in addressing cases of sexual violence against children and to identify obstacles encountered in handling such cases in Southwest Aceh Regency. Using qualitative methods, data were collected through in-depth interviews, observations, and documentation. The findings indicate that DP3A actively provides psychological and legal support to victims, conducts prevention outreach, and collaborates with police and relevant agencies during case management. However, the study also identifies several challenges, including limited literacy among village officials, a lack of clinical psychologists, budget constraints, and difficulties in reporting cases due to societal stigma. The research recommends enhancing cross-sector coordination, improving human resource capacity, and developing more responsive programs to meet the needs of children and families. Ultimately, this study aims to contribute to strengthening child protection efforts in Southwest Aceh Regency and serve as a reference for similar policies in other regions.